Ten-year retrospective evaluation of therapeutic choices and related satisfaction in patients with auricular deformities. Issue 7 (July 2022) - Vijverberg, M.A.; Siemann, I.; Verhamme, L.; Eising, H.; Damen, G.W.J.A.; Hol, M.K.S.
Abstract: To adequately counsel future patients with auricular abnormalities, this study aimed to analyze the therapeutic choices patients make after consultation concerning their auricle and/or hearing. All patients who visited the auricle consultation between January 2010 and January 2020 were included. This comprises patients with all types of auricular anomalies of both congenital and acquired etiology. Follow-up was performed by telephone to obtain informed consent and to take a short nonvalidated questionnaire regarding their therapeutic choices and satisfaction with these choices. Patient characteristics and information regarding therapeutic choices after consultation were subsequently obtained from the patients' medical files. The main outcome parameters were the patients' therapeutic choices regarding the auricle and hearing. A total of 134 patients (61.2%) were included with a mean follow-up of 3.85 years. For congenital and acquired etiologies, 72.8% and 18.2% declined reconstruction, 14.0% and 18.2% chose autologous, 5.3% and 0% chose alloplastic, 6.1% and 45.4% chose prosthetic, and 1.8% and 18.2% chose another type of reconstruction, respectively. A total of 54.9% declined hearing rehabilitation, while 38.2% chose percutaneous bone conduction device (BCD), 2.0% transcutaneous BCD, and 4.9% BCD on a softband. The overall satisfaction score was 8.7/10 concerning the auricle and 8.3/10 regarding hearing. In conclusion, most patients with a congenital etiology chose to wait or decided against auricular reconstruction, while patients with acquired etiologies mostly opted for reconstruction by a prosthesis. Patients or their caregivers were very satisfied with their choice, regardless of whether this implies reconstruction or no reconstruction, which emphasizes the importance of shared decision-making and thorough counseling.